2023
DOI: 10.1039/d3cy00549f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring CO2hydrogenation to methanol at a CuZn–ZrO2interfaceviaDFT calculations

Abstract: Multi-component heterogeneous catalysts are among the top candidates for converting greenhouse gases into valuable compounds. Combinations of Cu, Zn, and ZrO2 (CZZ) have emerged as promisingly efficient catalysts for CO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(35 citation statements)
references
References 90 publications
1
34
0
Order By: Relevance
“…In our previous study, we found that CO 2 attaches to the Cu component through the carbon atom with both oxygens binding to the nearest Zr cations. 17 The adsorption energy is −0.63 eV, which is comparable to that at the most stable adsorption site on ZrO 2 . Our earlier work demonstrated that incorporating Zn into the Cu matrix at the interface can strengthen CO 2 adsorption by up to 0.66 eV compared to the Cu-only interface.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In our previous study, we found that CO 2 attaches to the Cu component through the carbon atom with both oxygens binding to the nearest Zr cations. 17 The adsorption energy is −0.63 eV, which is comparable to that at the most stable adsorption site on ZrO 2 . Our earlier work demonstrated that incorporating Zn into the Cu matrix at the interface can strengthen CO 2 adsorption by up to 0.66 eV compared to the Cu-only interface.…”
Section: Resultsmentioning
confidence: 87%
“…3,4,13,15,17,81 From these results, one can conclude that certain sites are more optimal for the binding of different reaction intermediates, as some (such as COOH) adsorb more strongly to the Cu−ZrO 2 interface, while others (such as HCOO) bind on the ZrO 2 alone. A correlation has been identified between CO 2 adsorption strength and the binding of other intermediates, including COOH, HCO, and H 2 CO. 17 It should be noted that, although promising, the strongly exothermic CO 2 adsorption does not directly imply that later hydrogenation steps are selective toward methanol or other desired products. While the binding of further intermediates and their elementary reactions were excluded from the present study, the Zn y O z species may also act as favorable active sites for later hydrogenation steps.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations